Dr. Dimitrios Motakis — Deep Plane Facelift — Toronto - Motakis, Dimitrios (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Dimitrios Motakis, practicing in Toronto, Canada. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003166; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; canada; toronto